Evolutionary Dynamics and Pathogenicity Analysis of Feline Panleukopenia Virus in Xinjiang, China - Hanwen Zhang; Wenxiang Zhang; Yu Pan; Honghuan Li; Tao He; Qianqian Dong; Wenyan Song; Wenya Zhang; Liyan Zhang; Kashaf Kareem; Song Jiang; Jinliang Sheng (Microorganisms)
Feline panleukopenia virus (FPV), a globally pervasive and highly pathogenic pathogen, has garnered significant attention recently due to the cross-species transmission of its variants. Despite the vast body of research conducted on FPV, studies exploring its evolutionary history, dynamics, and the factors driving its evolution remain scarce. The pathogenicity of strains with the prevalent mutations (A91S and I101T) in the VP2 protein has also not been fully elucidated. This study conducted a comparative analysis of FPV VP2 sequences sourced from Xinjiang province in China, other provinces in China, and other countries. It was confirmed that the evolutionary rate of FPV approached that of RNA viruses, at approximately 1.13 × 10−4 substitutions/site/year. The study reconstructed molecular models of the VP2 protein with the A91S and I101T mutations and used viral strains carrying these mutations to perform the animal regression experiment. It was confirmed that isolates with the A91S and I101T mutations could cause typical leukopenia and acute enteritis symptoms, suggesting that the mutant strains still possess certain pathogenicity. This is the first study to report on the evolutionary dynamics of FPV in Xinjiang, China, and it emphasized the importance of continuously monitoring FPV evolutionary dynamics.